Probiotics in Orthopedics: From Preclinical Studies to Current Applications and Future Perspective - Antonio Mazzotti; Laura Langone; Alberto Arceri; Elena Artioli; Simone Ottavio Zielli; Simone Bonelli; Pejman Abdi; Cesare Faldini (Microorganisms, 2023)
In recent years, probiotics have been emerging as an attractive therapeutic strategy for several diseases. In orthopedics, probiotics seem to be a promising supplementation for treatment of osteoporosis, osteoarthritis, muscle loss-related disease, wound and ulcer issues, and prevention of surgical antibiotic prophylaxis side effects. Although probiotics are still not included in guidelines for these conditions, several studies have reported theoretical benefits of their administration. Further high-level clinical trials are necessary to convert research into solid clinical practice. However, probiotics represent a cost-effective future perspective and may play a role in association with traditional orthopedic therapies.